Pengembangan SDM Iptek (peneliti dan perekayasa) sebagai kunci keberhasilan Riset dan Teknologi di Indonesia - Setiawati, Asih (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
This study focuses on researcher human resources of government research and development institutions in Indonesia, who are facing the issues of low research and development outputs and minimum impacts to the market. Employing post-positivism paradigm, Â qualitative data collection method, it aims to examine the ideal development of future researcher HRs. The findings indicate that the research and development institutions had good awareness of the concept of human resource development, giving opportunities for researchers to learn. However, it is also revealed that the institutions were not on the right track in developing human resources, which includes trainings and development, and career and organization development. This research recommends the establishment of leader (management), both as the head of the program/team that acts as a team of change and a framework of integrated human resource development, comprising individual development aspects, career, and organizations accurately implemented using particular stages from analysis, design, implementation and evaluation. The need to conduct needs analysis of training and development. It has beenÂ  identified that prior to the analysis of training and development, track records of researchers, businesses with their databases, and activities of development and evaluation are needed as feedback for the team of change in the available human resource development theory.